Dinamika Dualistik Otomasi Bisnis: Analisis Kritis Anteseden Kinerja dan Tantangan Pada Bisnis - A A Ngurah Bagus Aristayudha Aristayudha; Vitalia Fina Carla Rettobjaan; Ni Made Widnyani; Kadek Riyan Putra Richadinata; Ni Luh Putu Surya Astitiani (Widya Manajemen, 2026)
The current phenomenon of business automation, encompassing technologies such as RPA and AI, has become a transformative mega trend that promises significant increases in productivity and profitability. Simultaneously, it raises risks of job displacement and ethical dilemmas. This research aims to critically analyze and synthesize scientific findings regarding the main drivers (antecedents), comprehensive impacts (consequences), and sectoral differences in the adoption of business automation. This study utilizes a Comprehensive and Systematic Literature Review approach, analyzing 50 highly relevant papers published between 2018 and 2025. The results identify five main drivers: Technological Readiness, Organizational Culture, Human Resource Involvement, External Pressure, and Perceived Benefits. The impact of automation is dualistic, providing operational gains while posing psychological and technical risks. This research provides a novel contribution by synthesizing a model that distinguishes automation dynamics across sectors and addressing the gap in existing literature that remains generalized and sector-undifferentiated.